2019
DOI: 10.1097/md.0000000000016723
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia is associated with poor in-hospital outcome in elderly patients with acute ischemic stroke

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
9
0
2
Order By: Relevance
“…Tight glycemic control in the management of acute ischemic stroke remains controversial due to the hypoglycemic consequences [32]. Despite the debate, the control of stress hyperglycemia and having it return to the normal range is of benefit to ischemic stroke subjects, as seen in experimental studies [4,33,34]. The homeostatic regulation of circulating glucose levels is strictly counterbalanced by gluconeogenesis, glycogenolysis, and glucose uptake as it occurred in the liver, adipose tissues, skeletal muscles, and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Tight glycemic control in the management of acute ischemic stroke remains controversial due to the hypoglycemic consequences [32]. Despite the debate, the control of stress hyperglycemia and having it return to the normal range is of benefit to ischemic stroke subjects, as seen in experimental studies [4,33,34]. The homeostatic regulation of circulating glucose levels is strictly counterbalanced by gluconeogenesis, glycogenolysis, and glucose uptake as it occurred in the liver, adipose tissues, skeletal muscles, and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…9 10 23 24 Masrur et al 9 studied 1408 patients who had AIS, who received intravenous thrombolysis and showed that high blood glucose levels at the time of admission increased the risk of unfavourable functional outcomes and death. Snarska et al 10 and Zhao et al 25 reported that a high blood glucose level in patients who had AIS at the time of admission was significantly associated with an unfavourable functional outcome and risk of in-hospital death. Moreover, several previous studies involving patients who had AIS without DM showed that high blood glucose levels were also closely related to unfavourable functional outcomes and risk of death.…”
Section: Open Accessmentioning
confidence: 99%
“…While the clinical and radiological features at the time of presentation are of great prognostic importance, other paraclinical features are also related to the severity of stroke and the course of the disease. Parameters such as mean blood pressure and mean blood glucose level, the nature of the antihypertensive drug used should also be considered 34‐36 . In light of all this information, it can be ensured that stroke patients are evaluated in all aspects, and perhaps a decision‐making model with all parameters can be created as a result of these studies.…”
Section: Discussionmentioning
confidence: 99%